Role of DNA Methylation and Epialleles in Eukaryotes: DNA Methylation & Epialleles - Jadoon, Linta; Naz, Shumaila; Rashid, Madiha; Zeeshan, Nadia; Khalid, Kainnat; Rauf, Sania (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Epialleles that emerge due to methylation variation in genetically identical individuals are gaining more interest due to their involvement in physiological and pathological processes. These are also important for transgenerational epigenetic inheritance and evolution. Both stable and metastable epialleles have their importance because of their contribution to the alteration of gene expression that may lead to useful traits or diseases. The main aim of this work lies in a comparative study between stable and metastable epialleles and the latest advancements that are helpful for the interpretation and analysis of DNA methylation and epialleles. However, there is so much to discover and understand because of the inadequate knowledge about methylomes of species as well as the naturally occurring epialleles in the wild. We will get more opportunities to apply this knowledge if we have a complete understanding of methylomes and epialleles and their contribution towards the normal functioning of an organism.